A novel equiaxed eutectic high-entropy alloy with excellent mechanical properties at elevated temperatures. Issue 10 (2nd October 2020) - Han, Liuliu; Xu, Xiandong; Li, Zhiming; Liu, Bin; Liu, C. T.; Liu, Yong
Abstract : A Co25.1 Cr18.8 Fe23.3 Ni22.6 Ta8.5 Al1.7 (at. %) eutectic high-entropy alloy (EHEA) consisting of face-centered-cubic (FCC) and C14 Laves phases was produced by powder metallurgy. The EHEA shows an equiaxed morphology that is different from eutectic lamellar structure. Nanometer L12 phase (4–5 nm) further precipitates in FCC matrix. The microstructure is highly stable upon annealing at 1000°C for 100 h, which leads to attractive high-temperature strength. The fracture behaviour is observed to be modified by the equiaxed Laves phase, which contains microcracks induced by multiple dislocation slips. The diversified cracking modes help to relieve stress concentration and therefore enhance ductility at high temperatures. GRAPHICAL ABSTRACT: UF0001 Impact statement: High-temperature tensile properties of a eutectic high-entropy alloy (EHEAs) are significantly improved compared to those of casted EHEAs, through modification of lamellar structure to an equiaxed one by powder metallurgy.